Gastrointestinal tract functional disorders in children under 1 year in Belgorod Region: prevalence, predicting factors and therapy - M. M. Gurova; E. A. Procenko (Сеченовский вестник)
We analyzed estimated the prevalence and predisposing factors of gastrointestinal tract functional diseases in children under 1 year in Belgorod Region. The survey involved 348 women with children aged 1 to 4 years. The main sections of the questionnaire dealt with the pregnancy, delivery and feeding details, antibiotics prescription in 1st year, the gastroenterological complaints and therapy. The functional disorders in children included regurgitation syndrome (18.3%), infant intestinal colic (74.4%) and constipation (33%). Predisposing factors were problematic pregnancy and delivery (31.3% and 25.3%, respectively), feeding (late breastfeeding and early termination of breastfeeding up to 3 months of life in 44% and 29.8%, respectively), antibiotic therapy in the first months of life - 23.6%.